2020
DOI: 10.1186/s12887-020-2004-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of undernutrition among children under-five years old in southern Ethiopia: does pregnancy intention matter? A community-based unmatched case-control study

Abstract: Background: Stunting, which describes a small height for one's age, is an indicator of chronic malnutrition. It develops mainly as a result of prolonged food deprivation or a chronic disease or illness. Unintended pregnancies and unplanned births are among the psychological factors that negatively affect the nutritional status of children. Therefore, this study aimed to determine the effects of unintended pregnancies and other family and child characteristics on the nutritional status of children under 5 years… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
9
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 24 publications
9
9
1
7
Order By: Relevance
“…Undesired girls are significantly associated with an increased likelihood of wasted and being underweight, similar to existing studies [ 12 , 51 ]. Shaka et al showed that children from unintended pregnancies were three times more likely to be stunted in southern Ethiopia.…”
Section: Discussionsupporting
confidence: 87%
“…Undesired girls are significantly associated with an increased likelihood of wasted and being underweight, similar to existing studies [ 12 , 51 ]. Shaka et al showed that children from unintended pregnancies were three times more likely to be stunted in southern Ethiopia.…”
Section: Discussionsupporting
confidence: 87%
“…Undesired children are signi cantly associated with an increased likelihood of stunting and underweight, similar to existing studies [50,51]. Shaka et al (2020) showed that children from unintended pregnancies were three times more likely to be stunted in southern Ethiopia. We also found the prevalence of overweight was higher among the desired children.…”
Section: Discussionsupporting
confidence: 82%
“…If a woman delivers more than she desires, then the children (either gender) may face a lack of proper caring, and the reluctance towards unwanted children may start from pregnancy. Shaka et al (2020) showed that children from unintended pregnancies were three times more likely to be stunted in Ethiopia. The share of childhood mortality from unintended pregnancies were also larger in sub-Saharan Africa [3].…”
Section: Introductionmentioning
confidence: 99%
“…15,16,20,23 However, un-intended pregnancy increases the odds of chronic undernutrition (stunting) among under-five children. 36 Whereas; fathers and mothers literacy, and higher wealth index decrease the odds of under-nutrition among under-five children. 10, 36, The trends of severe acute malnutrition in Kalafo district of Shebele zone remains high according to the routine therapeutic feeding program reports (TFP).…”
Section: Introductionmentioning
confidence: 99%